Clinical and Radiographic Evaluation of a Resin-Based Root Canal Sealer: 10-Year Recall Data - Osvaldo Zmener; Cornelis H. Pameijer (Hindawi Limited, 2012)
Objectives. This retrospective clinical and radiographical study evaluated the 10-year outcome of one-visit endodontic treatment with gutta-percha and a methacrylate resin-based sealer. Methods. From an initial sample size of 180 patients, 89 patients with 175 root canals responded to a recall. Treatment outcome was based on predetermined clinical and radiographic criteria. Results. Root canals had been adequately filled to the working length in 80 teeth (89.88%), short in 6 instances (6.74%), while 3 (3.37%) with extrusion immediate postoperatively, showed no sealer in periradicular tissues. The difference in the outcomes of treatments with respect to age, gender, preoperative pulp or periapical status, the size of periapical lesions and the type of permanent restorations were not statistically significantly different (𝑃>0.05). Overall, 7 (7.86%) cases were considered clinically and radiographically a failure. A life table analysis showed a cumulative probability of success of 92.13% after 10 years with a 95% confidence interval of 83.0 to 94.0. Conclusions. The results of this retrospective clinical and radiographical study suggest that the tested methacrylate-resin based sealer used with gutta-percha performed similarly to other root canal sealers over a period 10 years. Clinical Implications. Considering the success rate after 10 years of this methacrylate resin-based sealer can be recommended as an alternative to other commonly used root canal sealers.